Channels, carriers, and pumps an introduction to membrane transport - Stein, Wilfred D.; Litman, Thomas (Academic Press, 2015)
An introduction to the principles of membrane transport: How molecules and ions move across the cell membrane by simple diffusion and by making use of specialized membrane components (channels, carriers, and pumps). The text emphasizes the quantitative aspects of such movement and its interpretation in terms of transport kinetics. Molecular studies of channels, carriers, and pumps are described in detail as well as structural principles and the fundamental similarities between the various transporters and their evolutionary interrelationships. The regulation of transporters and their role in.